2019
DOI: 10.1111/ceo.13696
|View full text |Cite
|
Sign up to set email alerts
|

Auckland Cataract Study IV: Practical application of NZCRS cataract risk stratification to reduce phacoemulsification complications

Abstract: Importance: Reduction of intraoperative complications in phacoemulsification cataract surgery.Background: To assess practicability of a risk stratification system, the New Zealand Cataract Risk Stratification (NZCRS) system, in a major teaching hospital service, without investigator oversight, to ascertain whether benefits identified in research studies are maintained in busy clinical practice.Design: Prospective cohort study in a major public teaching hospital.Participants: Five hundred cases of phacoemulsifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…The pursuit in providing continuously better results after this kind of surgery, also due to higher patient expectations, push physicians to reduce the incidence of complications (26). For this reason, identifying and stratifying patient preoperative risk factors is a topic of increasing interest (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pursuit in providing continuously better results after this kind of surgery, also due to higher patient expectations, push physicians to reduce the incidence of complications (26). For this reason, identifying and stratifying patient preoperative risk factors is a topic of increasing interest (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, patient expectations induce physicians to limit the complication rate as much as possible and this is obviously more difficult in a teaching hospital. Today, intraoperative and postoperative cataract surgery complications are <10% and are usually mild and transient although in a few cases these events can lead to long-term visual dysfunction with strong dissatisfaction of patients (4). Most frequent intra-operative complications are posterior capsule rupture with or without vitreous loss (0.5-5.2%), intraoperative iris floppy syndrome or iris prolapse (0.5-2%) and iris or ciliary body injury (0.6-1.2%) (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank the author for his keen observations 1 in relation to our recent publication, the latest in the longitudinal Auckland Cataract Study (ACS) series IV: practical application of New Zealand Cataract Risk Stratification system to reduce phacoemulsification complications. 2 We agree that it is always worthwhile considering the utility of topical ocular antibiotics following routine small incision phacoemulsification surgery, given the relatively low incidence of endophthalmitis. 3 Indeed, with a reported incidence of 0.08%-0.35% 4 across a patient cohort eight times the size of the ACS IV 2 we agree that smaller studies, where patients routinely receive endophthalmitis prophylaxis involving povidone-iodine and subconjunctival cefazolin, lack the power to reveal clinical and statistical trends.…”
mentioning
confidence: 89%
“…We read with interest the recent article by Han et al regarding the Auckland Cataract Study (ACS) IV, noting there were no cases of post‐operative endophthalmitis reported (nor any in the current prospective ACS study of 2000 cases). This raised an interesting point in the utility of post‐operative topical antibiotics, which are almost universally prescribed despite a lack of evidence‐based practice.…”
mentioning
confidence: 91%